Life expectancy and health care spending in South Asia: An econometric analysis. - Bharat Ram Dhungana; Jitendra Kumar Singh; Samrat Dhungana (PLoS ONE)
Affordable health care is often a result of increased government spending on the health sector. Out-of-pocket expenses remain the primary health care funding source in many South Asian nations. Lack of adequate public funding for health services, difficulty in obtaining health insurance, and high out-of-pocket costs can result in indebtedness, reductions in actual consumption, and decreased access to health care services. The study examines life expectancy and health care spending in South Asian countries. The life expectancy of South Asian countries is studied as a health outcome in relation to health care spending, gross national income per capita, and expected years of schooling. This study is based on secondary data from World Bank statistics that covers eight South Asian countries from 2000 to 2021, for a total of 176 pooled time series and cross-sectional observations. The data were analysed using econometric models, including the cross sectional dependency test, panel unit root test, panel co-integration test, vector error correction model, pair-wise Granger causality test, and Wald test statistics. The vector error correction model results indicate that health care spending, anticipated years of schooling, and gross national income per capita have a long-run association with health outcomes. Health care spending, per capita gross national income, and expected years of education have all greatly enhanced life expectancy in South Asian countries. An effective health strategy is necessary to increase people's healthy life expectancy and well-being. To accomplish this, government may need to promote school enrolment to help people become more health literate and aware of their health outcomes. As a result, persons with more years of schooling have better health, higher levels of well-being, healthier habits, and ultimately, a longer life expectancy. This study will provide an important insight to policymakers in improving health outcomes through targeted and sustained health care spending in South Asia.